2019
DOI: 10.1039/c9na00248k
|View full text |Cite
|
Sign up to set email alerts
|

A MoS2–MWCNT based fluorometric nanosensor for exosome detection and quantification

Abstract: A MoS2-MWCNT based fl uorometric nanosensor for exosome detection and quantifi cationExosome detection and quantifi cation as an invaluable source of biomarkers can off er a non-invasive method for the early detection of diseases such as cancer. This work shows an effi cient and cost-eff ective method to quantify sub-populations of exosomes based on a fl uorometric technique. Utilizing multiwall carbon nanotubes coated with molybdenum disulfi de (MoS2-MWCNT) as a fl uorescence quenching material and an exosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The recognition and analysis of exosomes are the premise and guarantee in clinical research. [40] Therefor, the quantitative analysis of exosomes is of great significance. In order to improve the efficiency, sensitivity and reliability of exosomes analysis, many researchers proposed new analysis methods by specific recognition of exosomes, such as nucleic acid information, specific proteins, lipid recognition, surface modification recognition and overall recognition, etc., as shown in Figure 3.…”
Section: Methods Of Exosomes Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition and analysis of exosomes are the premise and guarantee in clinical research. [40] Therefor, the quantitative analysis of exosomes is of great significance. In order to improve the efficiency, sensitivity and reliability of exosomes analysis, many researchers proposed new analysis methods by specific recognition of exosomes, such as nucleic acid information, specific proteins, lipid recognition, surface modification recognition and overall recognition, etc., as shown in Figure 3.…”
Section: Methods Of Exosomes Detectionmentioning
confidence: 99%
“…Previous researches found that exosomes had an important impact on tumorigenesis, tumor metastasis and targeted therapy. The recognition and analysis of exosomes are the premise and guarantee in clinical research [40] . Therefor, the quantitative analysis of exosomes is of great significance.…”
Section: Methods Of Exosomes Detectionmentioning
confidence: 99%
“…The fluorescent antibodies would detach from MWCNTs when they bind to EVs, providing an LoD of 1480 EVs μL −1 . [113] In addition to fluorescence quenching based on carbon nanostructures, nucleic acid base pairing can also control fluorescent signals. A molecular beacon is a hairpin-shaped single-stranded DNA with an internally quenched fluorophore.…”
Section: Optical Sensorsmentioning
confidence: 99%
“…6b). 139,173,[176][177][178] Finally, polymeric NPs such as lanthanide chelate-doped polystyrene beads are also being used as sensing platforms. Islam et al used these NPs with long-lifetime fluorescence when compared with the fluorescence of highly effective markers, such as europium, to develop a NP-based time resolved fluorescence immunoassay (NP-TRFIA).…”
Section: Np-based Biosensors For Ev Analysismentioning
confidence: 99%